2021
DOI: 10.3389/fphys.2021.650190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ursolic Acid on Intestinal Health and Gut Bacteria Antibiotic Resistance in Mice

Abstract: Ursolic acid (UA), a natural pentacyclic triterpenoid, has been widely reported to exert anti-oxidant and anti-inflammatory properties. However, the effects of UA on the intestinal homeostasis and gut microbiota were rarely explored. The aim of the present study was to investigate the effects of UA on intestinal health and gut microflora antibiotic-resistance in antibiotic-exposed mice. Kunming mice (n = 80) were randomly allocated into three groups and fed with one of the following diets, respectively: Cont g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…Occludin, a key member of transmembrane protein, mainly regulate the permeability of TJs and maintain the polarity of epithelial cells ( 57 ). Consistent with previous studies ( 58 ), the protein concentration of Occludin and ZO-1 decreased after CS treatment in this experiment. Occludin protein did not display significant differences between CS group with YE or with RSM group, while both two kinds of algal oil improved the expression of ZO-1 in colon tissue compared with CS group.…”
Section: Discussionsupporting
confidence: 93%
“…Occludin, a key member of transmembrane protein, mainly regulate the permeability of TJs and maintain the polarity of epithelial cells ( 57 ). Consistent with previous studies ( 58 ), the protein concentration of Occludin and ZO-1 decreased after CS treatment in this experiment. Occludin protein did not display significant differences between CS group with YE or with RSM group, while both two kinds of algal oil improved the expression of ZO-1 in colon tissue compared with CS group.…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, recent studies have reported that gut microbiota dysbiosis and differentiation of Th17/Treg cells contribute to T1DM progression [ 11 , 17 , 42 ]. In addition, UA modulates the abundance and diversity of intestinal flora and inhibits Th17 cells differentiation [ 43 , 44 ]. However, whether UA has similar protective and ameliorative effects in T1DM remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression was determined on a real-time quantitative PCR system, using SYBR Green Premix Pro Taq HS qPCR kit (Accurate Biotechnology, Hunan, China). Relative quantification of the target gene expression was calculated as previously described methods ( Peng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%